2015
DOI: 10.1017/s0950268815002915
|View full text |Cite
|
Sign up to set email alerts
|

Assortative mixing as a source of bias in epidemiological studies of sexually transmitted infections: the case of smoking and human papillomavirus

Abstract: For studies examining risk factors of sexually transmitted infections (STIs), confounding can stem from the characteristics of the partners of study subjects, and persist after adjustment for the subjects' individual-level characteristics. Two conditions can produce confounding by the subjects' partners: C1) partner choice is assortative by the risk factor examined and, C2) sexual activity is associated with the risk factor. We term this bias the assortativity bias. The objective of this paper is to illustrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Recent modelling analyses of HPV and HIV, and of HSV‐2 and HIV, have suggested that observed associations could be explained by confounding by sexual risk factors, in the absence of biological interaction . However, these effects are likely to be greater for cross‐sectional studies whereas our review was based on longitudinal studies . Furthermore, we found some evidence in review 2 that adjustment for key confounding variables including sexual behaviour actually strengthened the associations.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Recent modelling analyses of HPV and HIV, and of HSV‐2 and HIV, have suggested that observed associations could be explained by confounding by sexual risk factors, in the absence of biological interaction . However, these effects are likely to be greater for cross‐sectional studies whereas our review was based on longitudinal studies . Furthermore, we found some evidence in review 2 that adjustment for key confounding variables including sexual behaviour actually strengthened the associations.…”
Section: Resultsmentioning
confidence: 70%
“…Conversely, mathematical modelling to assess potential biases in STI and HIV interaction estimates for different study designs has suggested that whilst statistical adjustment can help reduce overestimation due to confounding, the magnitude of association could also be underestimated in the presence of misclassification of exposure . Although we only included longitudinal studies, which established the sequence of events for HPV and HIV infections, there is still some potential for misclassification bias of both HIV and HPV exposure status.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3B). Unmeasured assortative mixing (44) and simultaneous exposure to multiple HPV types through sexual partnerships (45) can confound associations between HPV incidence and past exposures. Residual confounding may be a problem, because the initial infection risk is low and sensitive to host-specific risk factors.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of HSV-2 infection (particularly incident HSV-2 infection) might be a marker of having had sex with a partner infected with HIV because of the higher prevalence of HSV-2 among HIV-infected than among non-HIV-infected individuals. 76 , 77 , 78 Except for serodiscordant-couple studies, in which partner HIV status was known, few studies controlled for partner characteristics. Additionally, some studies inappropriately adjusted for genital ulcer disease, which might have biased pooled estimates toward the null value because HSV-2 commonly causes genital ulcers and these act as a point of entry for HIV.…”
Section: Discussionmentioning
confidence: 99%